HOTS Assessment of Biology Cell: Validity, Practicality and Reliability - Yosi Laila Rahmi; Nadiah Alhusna Miatidini; Heffi Alberida; Rahmawati Darussyamsyu; Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Titin Titin; Isil Koc; Maricar H Sison (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to produce an instrument for assessing high-order thinking skills about cell division material for students in class XII that are logically valid and empirically, practical and reliable. This study uses a 4D models development model consisting of the stages of defining, designing, developing, and disseminating. The dissemination stage was not carried out due to time and cost limitations. The subjects of this study were three validators consisting of two lecturers at the Department of Biology, Padang State University, and one teacher at Senior High School 2 Painan. Practicality was carried out by two biology teachers and 34 students of class XII of Senior High School 2 Painan. The data collection instruments were validation sheets and practicality tests. Data were analyzed using ANATES 4.09 application. The instrument for assessing high-order thinking skills about cell division material for class XII students who get an average logical validity value of 89.02% with valid criteria, the practical average value is 91.70% with very practical criteria. The empirical validity data analysis results obtained 37 questions out of 50 questions with a value of 74%, reliability of 0.89 with very high criteria. It can be concluded that an instrument for assessing the ability to think at a higher level about cell purchasing material is logically valid and empirically valid, practical, and reliable